1995
DOI: 10.1038/bjc.1995.229
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion changes in the RIF-1 tumour and normal tissues after carbogen and nicotinamide, individually and combined

Abstract: Summnu.aThe strategy of combining carbogen breathing and nicotinamide to overcome chronic and acute hypoxia respectively is being evaluated clinically. The effects of both agents individually and in combination on relative perfusion of 400-700 mm3 RIF-I tumours and normal tissues were measured by 'Rb extraction.Carbogen breathing alone for 6 min increased relative tumour perfusion by 50-700,<0 compared with control at flow rates of 50 to 200 ml min-'. but the effect was lost at 300 ml min-'. All flow rates als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The studies here show that in hepatoma 9618a the flow component is probably negligible because no increase in the average microregional blood flow was shown by laser Doppler measurements after carbogen breathing. This has also been observed in several other (Dewhirst et al, 1996;Powell et al, 1996;Hill et al, 1998), but not all (Honess and Bleehen, 1995) tumour types. Both increased oxygen tension and increased flow in response to carbogen breathing appear to be a tumour (type)-specific phenomenon (Hill et al, 1998).…”
Section: Discussionsupporting
confidence: 57%
“…The studies here show that in hepatoma 9618a the flow component is probably negligible because no increase in the average microregional blood flow was shown by laser Doppler measurements after carbogen breathing. This has also been observed in several other (Dewhirst et al, 1996;Powell et al, 1996;Hill et al, 1998), but not all (Honess and Bleehen, 1995) tumour types. Both increased oxygen tension and increased flow in response to carbogen breathing appear to be a tumour (type)-specific phenomenon (Hill et al, 1998).…”
Section: Discussionsupporting
confidence: 57%
“…Allowing the mice to breathe 10% CO 2 -90% O 2 caused blood flow to increase by an average of 50% (Kruuv et al, 1966). Similarly, it was recently shown that carbogen breathing for 6 min resulted in a 50-70% increase in blood flow in RIF-1 tumours growing subcutaneously in mice (Honess and Bleehen, 1995). In another study, Grau and coworkers could show no carbogen-induced change in blood flow in C3H mammary carcinoma growing in the feet of mice (Grau et al, 1992).…”
Section: Effects Of Different O 2 -Co 2 Breathing Mixtures On Tad Andmentioning
confidence: 88%
“…Hickam and Frayser, 1966) but there is evidence that carbogen decreases flow in some other tissues (Hampson et al, 1987;Honess and Bleehen, 1995). Furthermore, the vasoactive effects of carbogen appear to be dependent on route of administration, with mechanically ventilated animals responding with vasodilation, and freely breathing animals with vasoconstriction (Kallinen et al, 1991).…”
mentioning
confidence: 99%
“…Both these mechanisms would have to take account of the wellknown radiosensitizing effect of carbogen (Song et al, 1987) and of a recent report (Honess and Bleehen, 1995) that carbogen breathing causes an increase in RIF-l tumour blood flow. A fall in tumour blood flow lasting a few minutes would be unlikely to affect radiosensitivity unless the radiation were administered in that time window.…”
Section: Discussionmentioning
confidence: 99%